Identification of a novel membrane-associated protein from the S7 segment of grass carp reovirus. (28th January 2019) - Yu, Fei; Wang, Longlong; Li, Wanjuan; Lu, Liqun
Abstract : Aquareovirus is a genus of viruses in family Reoviridae, subfamily Spinareovirinae, members of which infect fish, shellfish and crustaceans. Grass carp reovirus (GCRV), a genotype 1 reovirus isolated from grass carp, has served as a model strain for investigating aquareovirus–host interactions. Herein, we report a neglected open reading frame (ORF), tentatively named NS12, residing between NS16 and NS31 in segment 7 (S7) of the virus genome. With an additional reading frame, the nucleotide sequence of NS12 partially overlaps with the 3′ expressible nucleotide sequence of NS16. NS12 is not a pseudogene during virus replication, as confirmed in fish cells infected with GCRV and based on amino acid sequence analysis and protein expression pattern. Bioinformatics analysis indicated that NS12 is a transmembrane protein, which was confirmed by its exclusive presence in the membrane-associated fraction of the cell lysate. However, unlike fusion protein NS16, NS12 alone could not induce visible syncytium formation in fish cells. Thus, NS12 is functionally distinct from known aquareovirus membrane-associated protein NS16. NS12-like ORFs (with an AUG or non-AUG initiator codon) are also present in the S7 segment of other aquareoviruses, suggesting that NS12 homologues may be widely distributed in the genus Aquareovirus .